Women, water, irrigation: respecting women's priorities - Shah, Anil C. (2002)
Transferring irrigation management to watger users'associations is considered essential for improving the canal management. Those, particularly NGOs committed to gender priority would like women to be brought in the `mainstream' of irrigation management by encouraging them to participate actively in the affairs of water users' associations. The paper that seeks to examine such an approach, begins with reporting on the interaction with women groups in six villages which had different sources of water for domestic use but one common feature - they were all served by a canal. Participatory rural appraisal conducted in these villages brought out that women's priority concern was very largely for water for domestic use. These women had hardly any interest in canal waters as they were perceived to be meant for agriculture, not for meeting `their' priority requirements. How can canals serve better the women priority needs for domestic use of water? What can women do for improving the canal management and better functioning of water users' associations. - Reproduced.
Keywords: Water; Irrigation; Women